A Constitutively Active Variant of the Quorum-Sensing Regulator LuxO Affects Protease Production and Biofilm Formation in Vibrio cholerae - Vance, Russell E. (American Society for Microbiology, 2003)
Vibrio cholerae normally inhabits aquatic habitats but can cause a severe diarrheal illness in humans. Its arsenal of virulence factors includes a secreted hemagglutinin (HA) protease. An HA protease-deficient mutant of V. cholerae was isolated and designated E7946 mpc. E7946 mpc was found to contain a point mutation in the luxO quorum-sensing regulator. In accordance with this finding, E7946 mpc exhibits a defect in quorum sensing. The mutant luxO allele [luxO(Con)] produces a protein with a leucine-to-glutamine substitution at amino acid 104. Transfer of the luxO(Con) allele to an otherwise wild-type background was sufficient to eliminate HA protease expression; conversely, deletion of luxO(Con) from E7946 mpc restored protease activity. We demonstrate that LuxO(Con) constitutively represses the transcription of hapR, an essential positive regulator of HA protease. Interestingly, strains harboring luxO(Con) form enhanced biofilms, and enhanced biofilm formation does not appear to be dependent on reduced HA protease expression. Taken together, the results confirm the role of LuxO as a central “switch” that coordinately regulates virulence-related phenotypes such as protease production and biofilm formation.